Adam Smith on vanity, domination, and history - Luban, D (Cambridge University Press, 2012)
Adam Smith's lectures present a bleak theory of history in which the innate human “love of domination” results in the perpetuation of increasingly repressive slave societies. This theory challenges common conceptions about the philosophical and historical foundations of Smith's thought, and accounting for it requires moving beyond traditional dichotomies between an “economic” sphere grounded on asocial wants and a “political” sphere grounded on sociability. For Smith, under the influence of earlier thinkers like La Rochefoucauld, Mandeville, and Rousseau, all human behavior is rooted in our esteem-seeking social nature, and the dominant form of esteem-seeking is a “corrupt” one based on external superiority. Understanding these foundations explains why Smith views both European commercial society and its central motive of economic self-interest as historically contingent, the product of a long series of unintended historical consequences.